The Mine-o-saur - Bardhan-Quallen, Sudipta (New York : Scholastic, 2007)
The greedy Mino-o-saur learns the hard way that he needs to share the toys in order to make friends.
Keywords: Dinosaurs -- Fiction; Sharing -- Fiction; Friendship -- Fiction